Does electronic trading influence stock prices? The Indian experience. Issue 18 (23rd October 2020) - Madhavan, Vinodh; Mukhopadhyay, Ishita; Ray, Partha
ABSTRACT: We study the impact of electronic trading in India via two distinct approaches. First, in a more traditional way, we model the data generating process (DGP) of share price index for different trading regimes using an AR-GARCH filter. Our results indicate regime-invariant nature of the DGP. Subsequently, we employ rolling Hinich Bicorrelation test to AR-GARCH-filtered standardized residuals to examine the degree of efficiency of Indian share price index across trading regimes. Our results indicate a distinct improvement in informational efficiency of Indian share price index pursuant to adoption of electronic trading systems.